The Benefits of Debate for English Students In Speaking Skills at University - Limbong; Sallata, Yizrel Nani; Arrang, Judith Ratu Tandi (Institut Agama Islam Negeri Palopo, 2024)
The purpose of this research is to find out about the benefits of debate on English students in speaking skills at UKI Toraja. Researcher use qualitative methods in research. This data was taken from 10 (ten) English students who were collected using a purposive sampling technique. To obtain data, researchers used interviews and analyzed using Sugiyono's theory. The results of the research show that there are several benefits of debate for English students in speaking skills, being involved in debate activities will be very beneficial for students, including how to convey arguments well, increasing students' self-confidence, improving logical and analytical thinking skills, can help students to improve new knowledge and also improve the ability to organize in a structured manner. Based on the results of the research above, the researcher concluded that students received several benefits from debate after participating in debate activities at UKI Toraja. Keywords: Benefits: English: debate; Speaking ability